Asymptomatic Bacteriuria in Pregnant Women - Hazhir, Samad (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: The aim of this study was to evaluate the frequency of bacteriuria in pregnant women referred to the medical centers of Tabriz, Iran, for prenatal care. Materials and Methods: A total of 1100 healthy pregnant women who were referred to 50 medical centers in Tabriz for a regular prenatal care were evaluated for bacteriuria. Results: The frequency of asymptomatic bacteriuria was 6.1%. Maternal age was lower in the women with a positive urine culture (P = .02). Asymptomatic bacteriuria had no relationship with gestational age, parity, level of education, and body mass index. Conclusion: We found a relatively high rate of bacteriuria in our cohort of asymptomatic pregnant subjects, especially the younger ones. For prevention from the complications of the asymptomatic bacteriuria in pregnant women, such as pyelonephritis, hypertension, preeclampsia, low birth weight, prematurity, septicemia, and even maternal and neonatal death, it is recommended to perform urine culture as a routine evaluation during the pregnancy.